2018
DOI: 10.1016/j.mimet.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis mouse model for the development of novel antigiardial agents

Abstract: This study describes a neonatal mouse model of Giardia infection for development of novel antigiardials. Mice were infected with the axenically cultured Assemblage A BAH2c2 strain, with 10 trophozoites per animal recovered. This model proved to be robust and consistent for use in preliminary drug efficacy trials and drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…As yet the drug target of these analogues remains undetermined. However, in our antibiotic studies with related compounds we observed that robenidine analogues affected the bacterial cell wall [31,32,36–39] . It is possible that a similar mechanism, against the trophozoite cell wall is in play.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…As yet the drug target of these analogues remains undetermined. However, in our antibiotic studies with related compounds we observed that robenidine analogues affected the bacterial cell wall [31,32,36–39] . It is possible that a similar mechanism, against the trophozoite cell wall is in play.…”
Section: Discussionmentioning
confidence: 64%
“…This would be in keeping with our electron microscopy observations of gross morphological changes to the dorsal cytoplasmic membrane of trophozoites, including membrane rupture. These effects would adversely affect the ability of the Giardia trophozoite to attach to membrane, interrupting a crucial stage in the parasite lifecycle, with the observed parasite killing [31,36] …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations